Constructing trade openness index for Pakistan - Zakaria, Muhammad (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2012)
This article constructs a trade policy openness index for Pakistan using quarterly data for the period 1981/82 to 2007/08. For this purpose theoretical and empirical literature on trade orientation measures is critically reviewed. It is found that every measure of trade orientation has some pros and cons. Therefore, one measure cannot be preferred to other measures nor any measure can be altogether relegated in favour of other measures. Following Wacziarg (2001), a trade policy openness index is calculated for Pakistan. This measure is objective, continuous and free from the omitted variable bias problem. Unlike other measures of trade openness in Pakistan, this measure is based on solid theoretical grounds as it incorporates both export and import tariffs and quantitative restrictions. It is concluded that this measure has considerable potential in empirical work regarding the trade openness-growth nexus in Pakistan
Argumenta Oeconomica, 2012, Nr 2 (29), s. 109-138
Keywords: exports; imports; trade openness